KLASIFIKASI KELAYAKAN PEGAWAI KONTRAK MENJADI PEGAWAI TETAP MENGGUNAKAN METODE NAIVE BAYES - Khoirudin, Muh. Rosyid; Hasbi, Muhammad; Widada, Bebas; Akhyar, Khoirul; Sandradewi, Kumaratih (STMIK Sinar Nusantara, 2024)
Employees are the most important asset in the ongoing activities and programs that have been designed by the foundation and the emergence of difficulties in determining the status of new staff at the foundation, because the manual system is still in effect, from written exams, oral exams and interviews. which allows the loss of files in testing and lack of objectivity in giving an assessment to employees. Therefore, this research was conducted to help determine the eligibility of foundation employees to be classified into